THE SCRIPT-TYPE COOPERATIVE LEARNING MODEL IN DEVELOPING CRITICAL THINKING SKILLS - Supriyadi, Agus; Eriyanto, Eriyanto; Muis, Abdul; Arfandi, Arfandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
The purpose of this study is to outline how the Script-Type Cooperative Learning Model is used at Asembagus 1 State Junior High School to help students in Islamic Religious Education, grade VIII A, enhance their critical thinking abilities. The significance of critical thinking abilities as a 21st-century talent that must be acquired via active, group, and purposeful learning serves as the foundation for this study.Descriptive qualitative research methodology was employed, and data was gathered by documentation, interviews, and observation. The Miles and Huberman model, which comprises data reduction, data presentation, and conclusion drawing, was used to examine the data. Triangulation of sources, methods, and time was used to assess the validity of the data.According to the findings, the Script-Type Cooperative Model was implemented in several steps, including pairing up, allocating resources, assigning speaker and listener roles, exchanging viewpoints, and coming to consensus. It has been demonstrated that using this technique enhances students' critical thinking abilities, as seen by signs like explaining, analyzing, forming conclusions, and posing and responding to questions. Additionally, education promotes social skills, the ability to voice one's thoughts, a sense of accountability, and the incorporation of Islamic principles into the educational process. The study's findings indicate that the cooperative script-type model works well for developing students' religious character and critical thinking abilities. This methodology merits further development in Islamic religious education as well as other subject areas, provided that teachers serve as facilitators and that the necessary infrastructure is in place.